The Book of Messages (Insha’) in Baghdad during the Buyid Era (334-447 AH / 945-1056 AD) - youssef, zainab; Mezel, Dr.Salam Ali (Thi Qar Arts Journal, 2025)
This research addresses the Book of Messages (Insha’) in Baghdad during the Buyid era (334-447 AH / 945-1056 AD). It is a study of the reasons for appointing the writers of this book and the reasons for their dismissal from their positions, as well as shedding light on the writers of the Abbasid caliphs during that era. The political authority was entrusted to the Buyid prince after the Buyids stripped the Abbasid caliphs of their previous powers in appointing and dismissing individuals from their administrative positions. The Buyid princes chose the best and most astute individuals for this position, giving them great status and consulting them on many matters.